Emerging 2D/0D g-C3N4/SnO2 S-scheme photocatalyst: New generation architectural structure of heterojunctions toward visible-light-driven NO degradation - Viet Van Pham (2022)
Enhancing and investigating the photocatalytic activity over composites for new models remains a challenge. Here, an emerging S-scheme photocatalyst composed of 2D/0D g-C3N4 nanosheets-assisted SnO2 nanoparticles (g-C3N4/SnO2) is successfully synthesized and used for degrading nitrogen oxide (NO), which causes negative impacts on the environment. A wide range of characterization techniques confirms the successful synthesis of SnO2 nanoparticles, g-C3N4 nanosheets, and 2D/0D g-C3N4/SnO2 S-scheme photocatalysts via hydrothermal and annealing processes. Besides, the visible-light response is confirmed by optical analysis. The S-scheme charge transfer was elucidated by Density-Functional Theory (DFT) calculation, trapping experiments, and electron spin resonance (ESR). We found that intrinsic oxygen vacancies of SnO2 nanoparticles and S-scheme charge transfer addressed the limitation of other heterojunction types. It is notable that compared pure SnO2 nanoparticles and g-C3N4, g-C3N4/SnO2 offered the best photocatalytic NO degradation and photostability under visible light with the removal of more than 40% NO at 500 ppb throughout the experiment. Benefiting from the unique structural features, the new generation architectural structure of S-scheme heterojunction exhibited potential photocatalytic activity and it would simultaneously act more promising for environmental treatment in the coming years.